2021
DOI: 10.1155/2021/7065910
|View full text |Cite
|
Sign up to set email alerts
|

Medical Monitoring and Management System of Mobile Thyroid Surgery Based on Internet of Things and Cloud Computing

Abstract: With the rapid development of the Internet of Things and cloud computing technologies, the Internet of Things technology based on comprehensive perception and interconnection and cloud computing based on virtualization, dynamic resources, and parallel computing have become the driving force for the innovation and development of informatization and intelligence. The cloud-based Internet of Things mobile medical is an ecosystem of health information and medical information, with the medical Internet of Things at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In this type of application, text messages will be sent directly to the user's mobile phone, and the content will cover a variety of topics, including detection and treatment methods, medical services, and disease management. Moreover, short messages can penetrate into relatively remote areas, where the level of public health education is low, and medical resources such as medical clinics and medical staff are also relatively limited [ 15 ] Health hotline: through a set of specific phone numbers, people can use their mobile phones to obtain more medical services, including telephone consultations, service complaints, medical facility information, medicines, medical equipment, and mobile medical clinics Diagnosis and treatment support: the application of diagnosis and treatment support is mainly to provide suggestions on diagnosis and treatment of patients for medical workers in remote areas, such applications can provide mobile phone applications, such as medical decision tree systems, to help medical workers make diagnoses, and can also provide diagnoses directly to patients [ 16 ]. Such cases are often referred to as “telemedicine,” where a patient can send a photo of a wound or condition to a remote physician as a reference for diagnosis.…”
Section: Evaluation and Correlation Analysis Methods Of Mental And Ps...mentioning
confidence: 99%
See 1 more Smart Citation
“…In this type of application, text messages will be sent directly to the user's mobile phone, and the content will cover a variety of topics, including detection and treatment methods, medical services, and disease management. Moreover, short messages can penetrate into relatively remote areas, where the level of public health education is low, and medical resources such as medical clinics and medical staff are also relatively limited [ 15 ] Health hotline: through a set of specific phone numbers, people can use their mobile phones to obtain more medical services, including telephone consultations, service complaints, medical facility information, medicines, medical equipment, and mobile medical clinics Diagnosis and treatment support: the application of diagnosis and treatment support is mainly to provide suggestions on diagnosis and treatment of patients for medical workers in remote areas, such applications can provide mobile phone applications, such as medical decision tree systems, to help medical workers make diagnoses, and can also provide diagnoses directly to patients [ 16 ]. Such cases are often referred to as “telemedicine,” where a patient can send a photo of a wound or condition to a remote physician as a reference for diagnosis.…”
Section: Evaluation and Correlation Analysis Methods Of Mental And Ps...mentioning
confidence: 99%
“…Diagnosis and treatment support: the application of diagnosis and treatment support is mainly to provide suggestions on diagnosis and treatment of patients for medical workers in remote areas, such applications can provide mobile phone applications, such as medical decision tree systems, to help medical workers make diagnoses, and can also provide diagnoses directly to patients [ 16 ]. Such cases are often referred to as “telemedicine,” where a patient can send a photo of a wound or condition to a remote physician as a reference for diagnosis.…”
Section: Evaluation and Correlation Analysis Methods Of Mental And Ps...mentioning
confidence: 99%
“…Researches show that the death caused by cerebrovascular diseases ranks first and second among the causes of death in China. The incidence rate of ischemic stroke accounts for more than 75% of cerebrovascular diseases [ 1 ]. In recent years, advanced technologies such as deep learning methods and mobile medical monitoring have been developed and widely applied in medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Results such as these are indicative that we have come to a point at which smart devices with Internet connections can provide fast and accurate measurements of clinical parameters in a reproducible manner and have the potential to effectively substitute an in-office visit for routine monitoring. In addition to the universally observed accuracy of the requested parameter measurements, distance monitoring saves time for the patient and the physician alike, prevents missed appointments and is generally preferred by patients [78][79][80]. When studying the response of bariatric patients postoperatively, regarding the telemonitoring process, Vilallonga et al found that patients themselves would prefer the telemonitoring option [71].…”
Section: The Role Of the Iot In Telemonitoring The Surgical Patientmentioning
confidence: 99%
“…Postoperative monitoring of physiological parameters with the use of biosensors can be further expanded to include automated action after the received sensor signal. In an example by Wang et al [75], patient-controlled analgesia was administered after indica- Within the surgical patient subgroup, there have been a few clinical studies looking into the applicability of telemonitoring, usually in the postoperative period [3,[65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80] (Supplemental Table S3). Patients enrolled in an at-home monitoring program after chest wall surgery were also monitored effectively by utilizing the Internet to input certain parameters in an online platform [65,67] Cardiac surgery patients were also studied in an IoST rehabilitation program that included wearable biomedical and motion tracking sensors [68].…”
Section: The Role Of the Iot In Telemonitoring The Surgical Patientmentioning
confidence: 99%